High yielding rice variety SEBERI 1 for irrigated lowland rice production systems in Niger - CGIAR Research Program on Rice (2020)
The high yielding irrigated lowland variety SEBERI 1 was released in Niger in 2020 after having been evaluated through the Africa-wide Rice Breeding Task Force network in multi-environment trials.